2018
DOI: 10.1111/head.13358
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders and Migraine: Review of Literature and Potential Pathophysiology Mechanisms

Abstract: Migraine shares a complex and poorly understood relationship with sleep. Patients consistently report poor sleep prior to migraine attacks and during them, identifying poor sleep as a migraine trigger. However, anecdotally, sleep is reported to serve a therapeutic role in terminating headache. Are the associations between migraine and sleep simply the result of various bidirectional relationships? A growing body of evidence suggests there may be a common underlying etiology as well. Our objective was to review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
125
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 78 publications
(137 reference statements)
2
125
0
1
Order By: Relevance
“…Across 12 studies, prevalence of headache varied greatly from 18 to 60% of apneics. 14 In the US, the case-control study found daily snoring was two-fold more common among individuals with chronic daily headache than episodic headache. 19 Nevertheless, considerable evidence does indicate that snoring should be considered.…”
Section: Evaluation and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Across 12 studies, prevalence of headache varied greatly from 18 to 60% of apneics. 14 In the US, the case-control study found daily snoring was two-fold more common among individuals with chronic daily headache than episodic headache. 19 Nevertheless, considerable evidence does indicate that snoring should be considered.…”
Section: Evaluation and Treatmentmentioning
confidence: 99%
“…A detailed review of sleep disorders related to migraine is presented elsewhere in this issue, 14 integrating new insights and latest neuroscience related to the glymphatic system to explain potential pathophysiological mechanisms underlying sleep disorders and migraine. Glymphatic activity is enhanced during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that patients with insomnia had a higher prevalence of migraine than did patients without insomnia; interestingly, patients with migraine who had insomnia reported more headache-related disability (as measured by the Headache Impact Test [HIT-6]) than patients with migraine but without insomnia. 17 A recent review of sleep disorders and migraine 18 provides an excellent overview of research into the relationship between the 2. [13][14][15] The relationship may be bi-directional, however.…”
Section: Introductionmentioning
confidence: 99%
“…For many individuals with migraine, the chronic nature of the disease significantly diminishes their quality of life and is isolating . In addition, depression, anxiety, and sleep disturbances are common comorbidities …”
Section: Introductionmentioning
confidence: 99%